Клініко-лабораторне тлумачення діабетичної нефропатії - Корольов, В. О.; Глушкова, О. В.; Репинська, І. Н. (Clinical Endocrinology and Endocrine Surgery, 2009)
The diabetic nephropathy (DN) is the leading reason of development of chronic illness of kidneys. The purpose of the present work — to estimate interrelation of the basic clinico-biochemical parameters in patients with DN at a type1 and 2 diabetes mellitus (DM). We investigated 148 inpatients with DM and DN. A level of glycated hemoglobin (HbA1c) defined a photometric method with application of incomplete hydrolysis of glycated protein with phosphoric acid and the subsequent photocolorimetry with 2-thiobarbituric acid at wave-length of 440 nm.